Goddess image, probably Parvati, housed within Charchoma Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha of the Charchoma Shiva Temple presently houses a Goddess image, probably Parvati, locally revered as Adi Shakti. The sculpture is dressed in such a way that the attributes and iconography of the Goddess sculpture are not discernible. There is a trident made of metal which is installed near the sculpture. Upon closer inspection, carvings of figures can be seen on the sides of the Goddess. But the figures are damaged, and their details are rubbed off.